Racial context and crime reporting: a test of Black's stratification hypothesis - Xie, Min (Journal of quantitative criminology, 2012)
Contextual factors that contribute to race differences in reporting crime to the police are an important element in Donald Black’s theory of the behavior of the law, yet few studies have investigated whether these differences vary depending on social context. The present study investigates whether the relationships between victim and offender race and the reporting of crime are moderated by the level of racial stratification in a given place as Black’s stratification hypothesis would predict. Using victim survey data from 40 metropolitan areas, as well as data from other sources, we find results that are consistent with Black’s stratification hypothesis, namely, that victim and offender race are more strongly associated with the reporting of crime in those metropolitan areas where the gap in economic status between blacks and whites is larger and the groups are more residentially segregated. The theory, however, is unable to account for the high rates of reporting of black-on-black assaults found across the 40 metropolitan areas. The question of how the needs of black victims may outweigh their reluctance to call the police is an important issue for future research.